Relationship of Attitude with Student Learning Environment Toward Physics - Putra, Dodi Setiawan; Irawan, Ardy; Yanto, Jelpapo Putra; Putra, Mecco Mandala; Adli, Syahrul; Dewi, Utari Prisma; Nasih, Neng Ria (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
The purpose of this study was to determine the description of student attitudes and learning environments towards physics and the relationship of student attitudes and learning environments towards physics at SMAN 6 Batang Hari. This type of research is quantitative using a correlational design with the instrument used is a questionnaire. The subjects of this study were 156 students from SMAN 6 Batang Hari. Quantitative data analysis techniques use descriptive and inferential statistics. The description for attitude is categorized as sufficient. While for the learning environment that is categorized good. The relationship between students' attitudes and learning environment towards physics is in the strong category with a pearson correlation of 0.719. Based on the results of SMAN 6 Batang Hari, the relationship between students' attitudes and the learning environment is strong for learning physics. Thus, positive student attitudes will be formed through a conducive learning environment.